Real-World Clinical Efficacy of Antifibrotic Agents for Idiopathic Pulmonary Fibrosis: A Single-Center Retrospective Study in Japan - Kotaro Iwasaki; Hiroki Wakabayashi; Atsuhito Saiki; Hajime Ueshiba; Yu Murakami; Yasuo Matsuzawa (Adis, Springer Healthcare, 2023)
Abstract Background The antifibrotic drugs, nintedanib and pirfenidone, inhibit the decline in forced vital capacity in patients with idiopathic pulmonary fibrosis (IPF). Nintedanib also inhibits the onset of acute exacerbation and reduces the risk of all-cause mortality. However, their effectiveness in real-world practice remains unclear. Our study aimed to investigate the changes in forced vital capacity, survival period, causes of death, and risk factors for mortality in patients with IPF receiving antifibrotic drugs. Methods This retrospective study enrolled Japanese patients who visited Toho University Sakura Medical Center who were diagnosed with IPF and received antifibrotic drugs. Results We included 102 patients [mean age ± standard deviation (SD): 71.8 ± 7.5 years], of whom 76 were males. The decline in forced vital capacity (mean ± SD) during the antifibrotic therapy period was − 154 ± 259 mL/year, which was significantly lower than before the antifibrotic therapy period (− 484 ± 589 mL/year; n = 80, p = 0.003). Altogether, 52 deaths were confirmed, and the median survival time from antifibrotic therapy initiation was 38.0 months (95% confidence interval: 25.9-50.1 months). Acute exacerbation accounted for 9.6% of all deaths (95% confidence interval: 1.6-17.6). The decline in forced vital capacity during antifibrotic therapy was a risk factor for mortality. Conclusions In actual clinical practice in Japan, antifibrotic drugs suppressed the gradual decline in forced vital capacity, which is a risk factor for mortality. However, the median survival period remained poor at 38 months.